Protecting women from image and eating-related difficulties: The promising role of body compassion and the bright side of non-striving - Santos, Mafalda Sofia Barata (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação